2013
DOI: 10.1111/rssb.12027
|View full text |Cite
|
Sign up to set email alerts
|

Covariate Balancing Propensity Score

Abstract: Summary The propensity score plays a central role in a variety of causal inference settings. In particular, matching and weighting methods based on the estimated propensity score have become increasingly common in the analysis of observational data. Despite their popularity and theoretical appeal, the main practical difficulty of these methods is that the propensity score must be estimated. Researchers have found that slight misspecification of the propensity score model can result in substantial bias of estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
1,004
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 1,030 publications
(1,022 citation statements)
references
References 68 publications
15
1,004
0
3
Order By: Relevance
“…In other words, the covariates need to be balanced between the two groups. Balancing covariates through propensity scores has been studied by several authors, including Austin (2008Austin ( , 2009), Imai and Ratkovic (2014) and Li, Morgan and Zaslavsky (2015). Rosenbaum and Rubin (1984) proposed using subclassification based on propensity scores, and Zanutto, Lu and Hornik (2005) provided an application of the subclassification method.…”
Section: The Propensity Score Adjusted Two-sample Empirical Likelihoodmentioning
confidence: 99%
“…In other words, the covariates need to be balanced between the two groups. Balancing covariates through propensity scores has been studied by several authors, including Austin (2008Austin ( , 2009), Imai and Ratkovic (2014) and Li, Morgan and Zaslavsky (2015). Rosenbaum and Rubin (1984) proposed using subclassification based on propensity scores, and Zanutto, Lu and Hornik (2005) provided an application of the subclassification method.…”
Section: The Propensity Score Adjusted Two-sample Empirical Likelihoodmentioning
confidence: 99%
“…The popular marginal structural model (MSM) for causal inference, of Robins et al, adjusts for time-varying confounding, but suffers from lack of robustness for misspecification in the weights. Recent work by Imai and Ratkovic [1] [2] achieves robustness in the MSM, through improved covariate balance (CBMSM). The CBMSM (freely available software) was compared with a standard fit of a MSM and a naive regression model, to give a robust estimate of the true treatment effect in 250 previously non-medicated adults, treated for one year, in a specialized ADHD outpatient clinic in Norway.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, what the CBPS estimation accomplishes is to estimate the propensity score such that the covariate balance is optimized. Imai and Ratkovic (2012) found that the resulting CBPS dramatically improves the empirical performance of propensity score weighting methods and overcomes the critiques of Kang and Schafer (2007).…”
mentioning
confidence: 99%
“…As discussed in Imai and Ratkovic (2012), the CBPS can be easily extended to nonbinary treatment regimes, which implies that it can be applied to the RMPW estimation even when the mediator is not binary. In particular, instead of fitting the ordered logistic regression via maximum likelihood as suggested by the authors, we can use the GMM estimation based on the following moment conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation